Spondylolysis with contralateral sclerosis: case report - Taşdelen, Neslihan; Gürses, Bengi; Yetimoğlu, F. Burcu; Kılıçkesmez, N. Özgür; Geler Külcü, Duygu; Kovanlıkaya, Arzu (Cerrahpaşa Medical Journal, 2014)
Unilateral spondylolysis with contralateral pedicle sclerosisis a relatively rare condition which may cause diagnostic difficulties and unnecessary surgical interventions. The purpose of this paper is to report two cases with radiologic findings and review the literature.